Improved Low-Delay MDCT-Based Coding of Both Stationary and Transient Audio Signals - Helmrich, Christian; Marković, Goran; Edler, Bernd (Proceedings of the IEEE 2014 Int. Conference on Acoustics, Speech and Signal Processing (ICASSP), 2014)
General-purpose MDCT-based audio coders like MP3 or HE-AAC utilize long inter-transform overlap and lookahead-based transform length switching to provide good coding quality for both stationary and non-stationary, i. e. transient, input signals even at low bitrates. In low-delay communication scenarios such as Voice over IP, however, algorithmic delay due to framing and overlap typically needs to be reduced and additional lookahead must be avoided. We show that these restrictions limit the performance of contemporary low-delay transform coders on either stationary or transient material and propose 3 modifications: an improved noise substitution technique and increased overlap between “long”transforms for stationary, and “long to short” transform length switching without lookahead and directly from the long overlap for transient frames. A listening test indicates the merit of these changes when integrated into AAC-LD.<br